PENGEMBANGAN SISTEM INTEGRASI PLUGIN GOOGLE MEET™ FOR MOODLE SKUTER (SISTEM KULIAH TERPADU) - Syamsul Alam Ramli; Nurdin S (Institut Agama Islam Negeri (IAIN) Palopo, 2022)
The PGPAUD Study Program at the University of Muhammadiyah Palopo in supporting the implementation of independent learning requires Lecturers to be more skilled and innovative in utilizing the SKUTER (Integrated Lecture System) or LMS IQRA Universitas Muhamamdiyah Palopo to the fullest. However, its use has not been maximized because the VICON (Video Converence) system is not yet available at the IQRA LMS Scooter at the University of Muhamamdiyah Palopo, making it difficult to communicate face-to-face. This study aims to develop a Google Meet™ For Moodle Plugin Integration System with a SKUTER (Integrated Lecture System) in the PGPAUD S1 Study Program, University of Muhammadiyah Palopo. This research method is educational research and development (Educational Research & Development) by adopting the Borg and Gall model which consists of 4 main steps, namely (1) objective analysis, (2) product development, (3) testing, and (4) implementation. The population in this study were lecturers and students of PGPAUD Muhammadiyah University of Palopo. Data collection techniques by collecting validation instruments and questionnaires, documentation. Data Analysis Techniques are carried out by using expert instrument data analysis techniques and data analysis techniques using practice. The results showed that the Google MeetTM Plugin on the course class page was functioning properly. There is a Google MeetTM Plugin Usage guide that users can access.